Development of Guided Inquiry Model Tools Assisted Palm Fiber Composite Media in Sound Wave Material - Selviana Haerani; Aris Doyan; Muhammad Taufik (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the feasibility, practicality, and effectiveness of the development of inquiry model learning devices guided by palm fiber composite media in sound wave material. The research method used is the research and Development (R&D) method with a 4D model consisting of definition, design, development, and dissemination stage.  Learning tools developed in the form of syllabus, Learning Implementation Plan (RPP), Learner Worksheet (LKPD), test instruments, palm fiber composite media, and learning video. Validation results show the learning device components in the category are so valid that they are feasible for use in learning.  Reliability of syllabus, Learning Implementation Plan (RPP), Learner Worksheet (LKPD), test instruments, palm fiber composite media, and learning video above 75% show all components assessed to be in the reliable category. The results of teacher response, student response, and learning implementation are in the very practical category. Learners' learning outcomes increased with a gain of 0.63 in the medium category. Based on these results, it can be concluded that the learning device of the guided inquiry model assisted by palm fiber composite media in sound wave material is feasible, practical, and effective.